Pemberdayaan UKS Kespro pada Remaja Putri di SMP Pertiwi 1 Kota Jambi - Hesty Hesty; Maimaznah Maimaznah; Muhammad Hidayat (3031-8572, 2025)
Reproductive health is a crucial aspect of individual and community life. Factors influencing reproductive health include social, economic, cultural, and environmental factors. School Health Units (UKS) are educational units' efforts to instill, foster, develop, and enhance healthy living skills. Reproductive health issues prevalent among adolescents represent a small fraction of the overall reproductive health problem. Therefore, one effort that can be taken is to establish and activate School Health Units. These School Health Units (UKS) play a crucial role in helping to increase knowledge about adolescent reproductive health through various means, including providing appropriate and correct education on adolescent reproductive health, so that students can obtain reliable information. The material was delivered through lectures, discussions, and Q&A sessions with participants using flipcharts. After the education, each young woman was asked to explain reproductive health to her friends and was divided into two groups. This was so that the Community Service team could monitor the young women's ability to educate their peers. The results showed an increase in knowledge of 90% and sufficient knowledge of 10%. It is hoped that the Health Unit (UKS) will continue to monitor the increase in knowledge of young women about reproductive health. This is certainly very necessary for young women who manage the UKS in managing the UKS related to reproductive health.